2000
DOI: 10.1016/s0022-5347(05)67041-3
|View full text |Cite
|
Sign up to set email alerts
|

Value of Routine Evaluation of the Voiding Phase When Performing Urodynamic Testing in Women With Lower Urinary Tract Symptoms

Abstract: Women with lower urinary tract symptoms may have voiding abnormalities that are missed by cystometrography only. Voiding studies are useful for properly diagnosing and treating such cases. Women with abnormal voiding seem to have more severe voiding symptoms than those without such abnormalities. Occult neurological disease may also be identified in patients with lower urinary tract symptoms and voiding abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 25 publications
1
13
0
2
Order By: Relevance
“…Furthermore, all women with a chief complaint of voiding or obstructive symptoms had bladder outlet obstruction, DO, or both. The most common voiding phase abnormality by far was dysfunctional voiding, which has been previously described in adult females [17]. Interestingly, none of the women in our study demonstrated impaired contractility.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Furthermore, all women with a chief complaint of voiding or obstructive symptoms had bladder outlet obstruction, DO, or both. The most common voiding phase abnormality by far was dysfunctional voiding, which has been previously described in adult females [17]. Interestingly, none of the women in our study demonstrated impaired contractility.…”
Section: Discussionsupporting
confidence: 60%
“…Thus, even in women without a chief complaint of voiding symptoms (only 23% in this study), the AUASI can be used to guide the clinician in deciding whether or not to perform urodynamics. This also highlights the benefits of performing routine evaluation of the voiding phase when performing urodynamics [17]. Women with bladder dysfunction had similar total and storage scores to those without bladder dysfunction.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Carlson et al [23] ont montré que la seule cystomanomé-trie ne permet pas d'identifier les anomalies de la phase mictionnelle. Il faut donc associer la cystomanométrie, qui étudie la phase de remplissage à des études de la [12], suffisamment bonne pour que ce critère soit respecté en pratique courante.…”
Section: Resultsunclassified
“…The remainder had anatomic causes such as prior surgery [6]. In a cohort of 36 obstructed patients, Carlson et al [7] found dysfunctional voiding in 16, primary bladder neck obstruction in six, DSD due to previously unsuspected neurologic disease in five, stricture in three, anatomic obstruction due to prior incontinence surgery in three, impaired contractility in two, and a urethral diverticulum in one. A review of 132 patients presenting with OAB symptoms who underwent videourodynamics found that 28% had benign prostate hyperplasia (BPH), and 11% had voiding dysfunction (bladder outlet obstruction [BOO], impaired contractility, or neurogenic bladder) [8].…”
Section: Dysfunctional Voiding Versus Bladder Neck Dyssynergiamentioning
confidence: 99%